Evaluation of the clinical significance of human papillomavirus (HPV) 53. (August 2015) - Padalko, Elizaveta; Ali-Risasi, Catherine; Van Renterghem, Lieve; Bamelis, Mieke; De Mey, Anja; Sturtewagen, Yolande; Vastenavond, Hilde; Vanden Broeck, Davy; Weyers, Steven; Praet, Marleen
Abstract: Objective: Human papillomaviruses (HPV) are classified according to their potential for the development of cervical neoplasia. However, the carcinogenicity of HPV types forms an evolving continuum based on the newly available data especially regarding the role of probable and possible high-risk HPV types (pHR-HPV). The objective of the present work was to evaluate clinical significance of the pHR-HPV53. Study design: An observational cohort study of potential aetiological association between infection with HPV53 and development of high-grade cervical cytology was performed. The study was conducted in two geographically remoted hospitals, in Belgium and Democratic Republic of Congo, as an attempt to collect data from regions with different geographical distribution of HPV genotypes. The samples were taken during routine gynaecological visit in outpatient clinics of both participating hospitals. Results: A total of 2283 liquid-Pap samples were taken from 1465 women at Ghent University Hospital, Belgium, and from 660 women at General Hospital and Ngaliema Hospital of Kinshasa, DRC. "HPV53-only"-pattern as evaluated by full HPV genotyping was found in samples from only 34 (1.6%) samples. The initial cytology represented next to non-dysplastic, undetermined and low-grade lesions also high-grade lesions (12%). For 26 (76.5%) from the 34 women presented with "HPV53-only"-pattern follow-up results were available showing no progression to malignancy. Conclusion: Our findings support very low to lacking carcinogenic potential of HPV53. Recognising extreme rarity in cervical cancer next to high prevalence in general population of HPV53, further studies investigating progression to high-grade lesions are needed to elucidate the oncogenic potential of pHR-HPV53.